Changing competitive dynamics in network industries: An exploration of sun microsystems' open systems strategy - Garud, Raghu; Kumaraswamy, Arun (Strategic Management Journal, 1993)
An integral part of competition is to deny rivals access to proprietary technical knowledge. Yet, Sun Microsystems provides rivals easy access to its technical knowledge and encourages them to enter its workstation market. This paper employs theoretical insights on technological systems and network externalities to understand Sun's open systems strategy. The paper also explores the changing nature of competition in network industries–industries characterized by network externalities and built around technological systems.